FRI0004 Randomization to Patient-Reported RAPID3 versus Physician-Based CDAI Tools for Prediction of Treatment Response and Assessment of Patient-Reported Outcomes in Rheumatoid Arthritis Patients Receiving Certolizumab Pegol: Results from the PREDICT Study. (10th June 2014) - Curtis, J.R.; Churchill, M.; Kivitz, A.; Samad, A.; Gauer, L.; Coteur, G.; Gervitz, L.; Koetse, W.; Melin, J.; Yazici, Y.
Abstract : Background: Guidelines support regular quantitative disease activity monitoring and early intervention in rheumatoid arthritis (RA), but there is no uniform agreement on the best measurement tool. 1, 2 While physician-based tools like the Disease Activity Score 28 (DAS28) and Clinical Disease Activity Index (CDAI) are commonly used, 3 the patient-based Routine Assessment of Patient Index Data (RAPID3) tool has also been shown to be able to distinguish active from control treatments in clinical trials. 4 Objectives: To compare the CDAI to the RAPID3 tool in RA patients (pts) 12 weeks (wks) after starting certolizumab pegol (CZP) and assess their ability to predict treatment success at Wk52 and to report patient-reported outcomes (PROs) from the PREDICT trial. Methods: In this 52-wk study (NCT01255761 ), pts received CZP standard dosing regimen (400mg at Wks 0, 2, 4 [loading dose], then 200mg Q2W). Pts were randomized 1:1 to RAPID3 or CDAI for classification as Responder/Non-Responder at Wk12. Treatment decision at Wk12 was based upon randomization arm (RAPID3 Responder, ≤6 or 20% improvement from Baseline [BL]; CDAI Responder, ≤10 or 20% improvement from BL). Treatment success at Wk52 was defined as DAS28(ESR) ≤3.2. PRO endpoints included assessment of physical function, pain, disease activity and symptomatic state. The results are presented for the full analysis set (FAS); for efficacy results, both arms were adjusted for BL covariates, including DAS28(ESR) scores. Results: At Wk12, 64.7% and 76.4% of pts randomized to RAPID3 and CDAI, respectively, were classified as Responders (Table). At Wk52, 31.5% of Wk12 RAPID3 Responders and 32.3% of Wk12 CDAI Responders achieved DAS28(ESR) low disease activity (LDA), and 21.8% and 23.2% achieved remission, respectively, demonstrating similar positive predictive values of these measures (Table). Pts reported improvements for physical function (MDHAQ-FN), pain (PtAAP), disease activity (PtGADA) and symptomatic state (PASS) as early as Wk2, which continued to Wk12 and were maintained to Wk52. Similar changes were observed in PRO measures of both groups. Conclusions: The physician-based assessment detected greater CZP response at Wk12, compared with the patient-reported tool. The positive predictive value for LDA at Wk52 for both assessments was similar. Further analysis is needed to evaluate the sensitivity and specificity of these measures for disease activity assessments and treatment decisions in RA. Improvements in PROs were observed in both groups as early as Wk2 and were maintained to Wk52. References: Saag K.G. Arthritis Rheum 2008; 59(6):762-784; 2. Smolen J.S. Curr Med Res Opin 2011; 27(2):315-325; 3. Anderson J. Arthritis Care Res 2012; 64:640-647; 4. Castrejόn I. Clin Exp Rheumatol 2012; 30:S50-55 Acknowledgements: The authors acknowledge Costello Medical Consulting for writing and editorial assistance which was funded by UCB Pharma. Disclosure of Interest: J. Curtis Grant/research support: Roche, Genentech, UCB Pharma, Janssen, CORRONA, Amgen, Pfizer, BMS, Crescendo, AbbVie, Consultant for: Roche, Genentech, UCB Pharma, Janssen, CORRONA, Amgen, Pfizer, BMS, Crescendo, AbbVie, M. Churchill: None declared, A. Kivitz Grant/research support: Abbott, Pfizer, Merck, Janssen, Novartis, Celgene, UCB Pharma, Consultant for: Abbott, Pfizer, Janssen, Celgene, UCB Pharma, A. Samad Employee of: Ardea Biosciences, L. Gauer Employee of: UCB Pharma, G. Coteur Employee of: UCB Pharma, L. Gervitz Employee of: UCB Pharma, W. Koetse Shareholder of: UCB Pharma, Employee of: UCB Pharma, J. Melin Employee of: UCB Pharma, Y. Yazici Grant/research support: BMS, Genentech, Celgene, Consultant for: Abbvie, BMS, Celgene, Genentech, Pfizer, Samumed, UCB Pharma DOI: 10.1136/annrheumdis-2014-eular.1674